Planning and Implementation of Small Towns: A Case Study of Longsha Town, Wanzhou District - Qiao, Na (Journal of Theory and Practice of Management Science, 2024)
In the process of rural revitalization, the construction of small and medium‐sized towns is going on vigorously. On the basis of the traditional urban master plan, it is the control planning and then the construction planning. There is a lack of an effective connection between the planning and construction. Therefore, all regions begin to realize this connection through a series of guidelines. On the one hand, it summarizes the contents of planning, on the other hand, it guides the construction of small towns to play an important role in leading the ecological, healthy and characteristic small towns. Higher Vocational College is an important strategic position to cultivate applied talents in the field of education in China, and physical education is an essential course in higher vocational colleges. From the perspective of vocational education background, physical education curriculum education in higher vocational colleges should be improved and innovated with the change of educational objectives and teaching forms, to ensure higher efficiency and quality of personnel training. Therefore, this paper mainly discusses the innovation and development of physical education in Higher Vocational Colleges with vocational education as the leading background, with the purpose of promoting personnel training to a higher level, making students more professional and professional, to promote students' vocational skills and have better core competence in social work in the future.